2023
DOI: 10.3390/healthcare11202712
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Longitudinal Relationship between Changes in Depression and Cognitive Function among Older Adults Living Alone

Soyoung Park,
Kyuhyoung Jeong,
Seoyoon Lee

Abstract: Background: As South Korea faces unprecedented population aging, this longitudinal study examined the relationship between depression and cognitive function changes in older individuals living alone. Methods: The study used data from the Korean Longitudinal Study of Aging (KLoSA). A total of 1354 participants with data available over a period of at least three years, from 2016 (wave 1) to 2020 (wave 8), were included, and latent growth modeling (LGM) was used for analysis. Results: Depression levels increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…According to a World Health Organization report published in 2021, more women are affected by depression than men. Some studies have also shown that epidemiological gender differences in depression are well characterized (7)(8)(9)(10)(11). Women are more likely to suffer from depression throughout their lives and are twice as prevalent as men (12).…”
Section: Introductionmentioning
confidence: 99%
“…According to a World Health Organization report published in 2021, more women are affected by depression than men. Some studies have also shown that epidemiological gender differences in depression are well characterized (7)(8)(9)(10)(11). Women are more likely to suffer from depression throughout their lives and are twice as prevalent as men (12).…”
Section: Introductionmentioning
confidence: 99%